Perbandingan Pengaruh Konsentrasi Biotin dan Varietas Pisang Barangan dan Cavendish Terhadap Pertumbuhan Eksplan Pada Kultur In Vitro - Fitria, Fitria; Eliyanti, Eliyanti; Riduan, Ahmad; Zulkarnain, Zulkarnain; Ichwan, Budiyanti (Universitas Batanghari, 2024)
This study aims to investigate the effect of Biotin vitamin on the growth of in vitro shoot explants from Barangan and Cavendish banana varieties and to determine the optimal Biotin concentration. The research employed tissue culture techniques using Murashige and Skoog (MS) medium and a Completely Randomized Design (CRD) with a total of 144 culture bottles. The results indicate that the addition of Biotin significantly influences the growth of both varieties. The Cavendish variety exhibited a better response than Barangan, with a Biotin concentration of 2.5 ppm yielding the best results in terms of shoot number, shoot length, and faster shoot formation time. Meanwhile, for the Barangan variety, a concentration of 0.5 ppm accelerated shoot formation, while a concentration of 2 ppm resulted in the highest shoot number and length. The conclusion of this study suggests that higher Biotin concentrations can enhance the growth of shoot explants, particularly in the Cavendish variety. These findings may serve as a basis for the more efficient development of banana seedlings through in vitro methods. Further research is necessary to evaluate the efficiency during the acclimatization stage in the field.